The Relationship between Coping Mechanisms and Anxiety in Basic Professional Nursing Students at the Faculty of Health Sciences, Muhammadiyah University of Jember - Zubair , Ilham Ainullah; Suryaningsih , Yeni; Sasmiyanto, Sasmiyanto (International Applied Science, 2023)
Students who want to undertake basic professional nursing generally have varying levels of anxiety. The anxiety that students often experience is related to the basic professional nursing program, such as the first time carrying out clinical practice and feelings of anxiety because there are different things that have never been done before. , feelings of worry regarding the possibility of events causing harm to the patient, due to insufficient knowledge and experience. The design used is correlational research whose aim is to find a correlation between the two variables being studied using a cross sectional approach . The population in this study is fifth semester students with a sample size of 103 students from the Nursing Science Study Program. The sampling technique used is simple random sampling. Data analysis in this study used the Spearman Rho statistical test. Spearman's rank statistical test, namely the value of p = (0.001) and alpha < 0.05, which means there is a relationship between Coping Mechanisms and Anxiety in Basic Professional Nursing Students at the Faculty of Health Sciences, Muhammadiyah University of Jember, with a value of r = -0.319 with the strength of the relationship moderate or moderate. There is a relationship between coping mechanisms and anxiety in basic professional nursing students at the Faculty of Health Sciences, Muhammadiyah University of Jember. Students who are carrying out basic professional nursing learning activities are able to reduce anxiety by increasing coping by doing positive things, so that students can make the right decisions. This can be done by reading books or doing more practice to increase insight and experience.